Typifications and nomenclatural clarifications in South American Tagetes (Asteraceae, Tageteae) - Schiavinato, Dario J.; Gutiérrez, Diego G.; Bartoli, Adriana (Phytotaxa, 2017)
During the course of the revision (in progress) of the South American species of Tagetes, we detected the need for nomenclatural clarifications and typifications in order to correct application of taxa´s names. We analyzed protologues, biographies of authors and collectors, original and common materials, and morphological traits. As a result we clarified author citations of T. anisata and T. pseudomicrantha, and type localities of several taxa. In addition, we designated 12 lectotypes and two epitypes for the following plant names: T. anisata, T. bonariensis, T. campanulata, T. dianthiflora, T. mandonii, T. maxima, T. microglossa, T. multiflora var. rupestris, T. peduncularis, T. porophyllum, T. pseudomicrantha, T. tenuifolia, and T. zypaquirensis.